UTILIZATION OF GEOLOCATION FOR MONITORING DUAL SYSTEM EDUCATION - Rosnani (Yayasan Nusantara Hasana Berdikari, 2023)
Implementing Dual System Education (DSE) for SMK Tut Wuri Handayani students for 3 months requires the guidance teacher to visit the industry where DSE is implemented. However, if teachers cannot attend because of other activities that cannot be postponed, then visits to the industry where DSE is carried out will be hampered. For this reason, an application or system is needed that can be used to solve the problem of industrial visits to the DSE place. The research that has been carried out produces an application or geolocation system to monitor the attendance and activities of students in places implementing DSE